Second supplement for the genus Phlugiolopsis Zeuner, 1940 (Orthoptera: Tettigoniidae: Meconematinae) from China, with eight new species - Bian, Xun; Shi, Fu-Ming; Chang, Yan-Lin (Zootaxa, 2013)
This paper deals with 8 new species of Phlugiolopsis from Yunnan and Guizhou, China, supplements the images of P. ventralis Wang, Li & Liu, 2012 and details the morphology of male stridulatory files and mandibles for 9 Phlugiolopsis known species. Distribution of poorly known species and new species are presented. A key to all known species is provided. Based on the known distribution of Phlugiolopsis and bioclimatic variables in WorldClim, we used the ecological niche models, maximum entropy (Maxent), to predict the potential geographic distribution of the genus. All specimens are deposited in the Museum of Hebei University.